Bittersweet - Adrian M. Schnall (Case Western Reserve University, 2021)
The winner has been declared. A flood of relief! Exultation!  Dancing in the streets! And a gasp of horror. How can there be tens of millions  on the other side? So many more than a couple dozen Proud Boys, a few towns of hillbilly farmers,  a frenzied rally crowd  chanting Lock her up. It's fathers and mothers,  sisters and brothers, face upon human face. Is it them or us?  Who are the blind?  Fires still flare on the battlefield -  one is raging on and off in the distance.   But every blaze is dying as I watch.   Great conflagrations  are turning to ash. The forecast is for snow on the mountaintops, in the streets, in the corridors of State. Pride needs to go  into hibernation. I think the air will be clear in the morning. I think I will hear  music in the trees. But no one is surrendering his gun.